The use of art therapy methods in the mental development of preschool children and in overcoming negative mental states. (Texas Journal of Multidisciplinary Studies, 2024)
This article describes the use of art therapy methods in the mental development of preschool children and the elimination of negative mental states and the correction of negative mental states through art therapy. A description of exercises that provide mental peace is presented